The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3855/jidc.1339
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a newly developed ELISA against Widal, TUBEX-TF and Typhidot for typhoid fever surveillance

Abstract: Introduction: Typhoid fever is endemic in many parts of the world and represents a major cause of acute febrile illness (AFI). Rapid and accurate laboratory methods for diagnosis of this disease are needed for both patient care and surveillance situations. Methodology: Serum samples were collected from AFI patients and used to evaluate the performance of a newly developed ELISA assay that uses a mixture of somatic and flagellar antigens to detect the total antibody response against Salmonella enterica subspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Furthermore, blood culture sensitivity was optimized in our study because we used modern blood culture techniques. 28 Our findings on the Widal test and the newer typhoid rapid antibody tests are similar to those from studies conducted in Asia and Egypt; [8][9][10]25,29,30 none of the rapid tests performed nearly as well as blood culture for the diagnosis of typhoid fever. Some reports suggest that the Typhidot ® test may be more useful in Asia.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, blood culture sensitivity was optimized in our study because we used modern blood culture techniques. 28 Our findings on the Widal test and the newer typhoid rapid antibody tests are similar to those from studies conducted in Asia and Egypt; [8][9][10]25,29,30 none of the rapid tests performed nearly as well as blood culture for the diagnosis of typhoid fever. Some reports suggest that the Typhidot ® test may be more useful in Asia.…”
Section: Discussionsupporting
confidence: 72%
“…While the TUBEX ® test was the most sensitive and specific in the Philippines, 6 neither TUBEX ® nor Typhidot ® was both sensitive and specific in two evaluations undertaken in Viet Nam 7,8 and performance was poor in a trial conducted in a community clinic in Bangladesh 9 and in a study in Egypt in which it was compared with a new ELISA not yet commercially available. 10 Rapid typhoid tests have not been evaluated in subSaharan Africa, where the typhoid fever burden may be smaller than in Asia. [11][12][13] The World Health Organization (WHO) has issued no recommendations on the use of typhoid rapid antibody tests.…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has been put into improving on the classic Widal test over the last twenty years specifically in order to improve the speed and reliability of serological testing (Bhutta & Mansurali, 1999;House et al, 2001;Gasem et al, 2002;Hatta et al, 2002;Jesudason et al, 2002;Olsen et al, 2004;Tam et al, 2008;Fadeel et al, 2011). Several of these assays have subsequently become commerically available; Typhidot® (Malaysian Biodiagnostic Research SDN BHD, Malaysia) and TUBEX assays (IDL Bideh, Solletuna, Sweden) are discussed in further detail below.…”
Section: Serological Testsmentioning
confidence: 99%
“…In some studies, it has shown that for total Ig estimation ELISA has superior sensitivity when compared to other tests. 64 Recently DNA probes and polymerase-chain-reaction (PCR) have been developed to detect S. enterica serotype typhi directly in the blood. 53,58 Urine antigen detection has 65-95% sensitivity.…”
Section: New Diagnostic Toolsmentioning
confidence: 99%